Repair of Lafosse I subscapularis injury adds no additional value in anterosuperior rotator cuff injury - Binghao Zhao (BMC, 2021)
Abstract Background The study aimed to explore the additional value of repair of Lafosse I subscapularis injury compared with debridement in anterosuperior rotator cuff injury. Methods The prospective study was conducted on a total of 41 patients with supraspinatus tendon tear combined with Lafosse I subscapularis injury. Eighteen patients were divided into the repair group and 23 patients were divided into the non-repair group. The two groups were compared for intraoperative parameters, pain score, range of motion of the shoulder joint, shoulder joint function and quality of life (QoL) at pre-operation, 3 and 6 months postoperatively and the final follow-up visit. Results The width of supraspinatus tendon tear did not exceed 3 cm and did not retract beyond the glenoid in among patients. There was no statistical difference of preoperative data between two groups, including age, course of disease, positive Jobe test, positive Bear-hug test, positive Lift-off test, Patte stage, longitudinal tear and pain severity (P > 0.05). Compared to preoperative levels, the severity of pain, ASES scores and EQ-5D-3L scores were significantly lower at 3 and 6 months postoperatively and the final position (P < 0.05). However, there was no statistical difference in pain severity, ASES scores and EQ-5D-3L scores between repair group and non-repair group (P > 0.05). Similarly, compared to preoperative levels, the range of motion of shoulder joint was significantly improved after operation, including internal rotation, external rotation, forward flexion and elevation (P < 0.05). However, there was no statistical difference in range of motion of shoulder joint between repair group and non-repair group (P > 0.05). Conclusion Operative treatment can effectively lessen severity of pain in the patients, improve shoulder joint function, increase the range of motion of the shoulder joint and enhance the QoL in treating anterosuperior rotator cuff injury. However, repair of subscapularis brings no benefit compared to debridement in treating supraspinatus tendon tear combined with Lafosse I subscapularis injury.